POLITIK HUKUM IMPLEMENTASI KESADARAN BELA NEGARA SUMBER DAYA MANUSIA DALAM MENJAGA PERTAHANAN DAN KEUTUHAN NKRI BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2019 TENTANG PENGELEOLAAN SUMBER DAYA NASIONAL UNTUK PERTAHANAN NEGARA - Hasbullah Alimuddin Hakim; Alexander Pane; Wahyu Dwi Erlangga (Universitas Muhammadiyah Jember, 2020)
This writing discusses the defense of the state is an attitude and act of awareness of citizens based on a sense of patriotism, national and state awareness, Pancasila beliefs as an ideology of the nation, willingness to sacrifice to face any threats, challenges, obstacles and disturbances both coming from within and from outside which endangers the survival of the nation and the State, the integrity of the Unitary Republic of Indonesia, national jurisdiction and the noble values of the Pancasila and the 1945 Constitution. This legal research uses prioritizing the literature and legal document approach as well as materials from various secondary data that reviews the regulations. regulations, opinions of legal experts, books, papers, journals, legal materials from intermet and others relating to legal issues concerning the Political Law of the Implementation of Defending State Awareness in Maintaining Defense and Integrity of the Republic of Indonesia based on Law Number 23 of 2019 concerning Management of Resources National Power for Pert State Services This research results that the Legal Political Construction Implementation of state defense through Human Resources is divided into two periods namely the Reformation Period and the Post-Reformation Period and the Implementation of State Defending Awareness is the right and obligation of every citizen who is certain to be able to uphold the country's sovereignty in maintaining Defense and the integrity of the Unitary Republic of Indonesia research methods are normative juridical, namely research that is Keyword Political Law, Defending the National Defense and the Unitary Republic of Indonesia.